53 Invasive angiography following FFRCT – a real world nhs experience. (17th July 2020) - Murphy, David; Graby, John; McKenzie, Dan; Kandan, Raveen; Augustine, Daniel; Lowe, Rob; Mansfield, Richard; Easaw, Jacob; Garg, Anu; Carson, Kevin; Hudson, Ben; Rodrigues, Jonathan
Abstract : Introduction: Computed Tomography Coronary Angiography (CTCA) is NICE recommended as the diagnostic investigation of choice for patients presenting with stable angina. The technology is well recognised for providing coronary anatomy and descriptive analysis of coronary disease. Fractional Flow Reserve derived from CTCA (FFRCT) is an additional, FDA approved non-invasive technique for defining the probability of flow-limiting coronary artery stenosis that correlates with invasive FFR measurements. Previous studies undertaken at this District General Hospital highlighted the value of this tool in streamlining invasive strategies. This follow-up study sought to assess the next step in the patient pathway, comparing those identified as intermediate to high risk based for flow limiting disease on FFRCT with the findings and management strategy employed at subsequent invasive coronary angiography. Methods: A retrospective analysis of all CTCA's (SOMATON Definition edge, Siemens) reports between April 2018 and January 2019 with FFRCT (Heartflow Inc.) undertaken were reviewed. Any imaging that reported an intermediate to high risk of flow limiting coronary disease based on FFRCT were included, (values of <0.75 = High likelihood of flow-limitation; 0.75 - 0.80 = Intermediate). These were then compared to the strategy employed at invasive angiography, and invasive pressure wire assessments where undertaken. Results: A total of 108 studies were sent for Heartflow analysis, of which 27 had intermediate or high likelihood of flow limiting coronary disease reported and have had subsequent invasive angiography. This consisted of 60% male, with a mean of age 67 (range 42-83 years). Invasive pressure wire assessment via iFR (instantaneous wave free ratio) and/or FFR was carried out in 9 (33%) patients at angiography. In total, 43 vessels with FFRCT intermediate or high likelihood vessels were assessed invasively. Table 1 below outlines the FFRCT findings versus invasive angiography management. FFRCTInvasive Coronary angiogram iFR/FFR -veiFR/FFR +veDirect Re-vascularisation (PCI)Direct Re-vascularisation (CABG)Not Invasively assessed Intermediate73115 High0112103 Table 1 . This table compares FFRCT findings with invasive angiography strategy / findings. Of the 3 vessels with 'high probability of flow-limiting disease' that were not invasively assessed, all were branch vessels (2 diagonals and 1 obtuse marginal). Conclusions: This study represents a real world NHS experience of activity undertaken in the catheter lab when functional information of coronary flow is known in advance of an invasive procedure. In some cases (13/16 [81%] of patients with a high probability of flow limiting disease) a direct decision on re-vascularisation was taken by the operator without further invasive pressure wire assessment, which may have reduced procedure duration. Further experience with FFRCT may increase operator confidence and thus increase the frequency of proceeding directly to re-vascularisation where indicated, thus reducing both procedure and fluoroscopic screening times. A further assessment of the role of FFRCT employed for stent planning pre-procedure is intended. Conflict of Interest: None